An ancient protein phosphatase, SHLP1, is critical to microneme development in Plasmodium ookinetes and parasite transmission. - Patzewitz, E; Guttery, D; Poulin, B; Ramakrishnan, C; Ferguson, D; Wall, R; Brady, D; Holder, A; Szöőr, B; Tewari, R (2013)
Signaling pathways controlled by reversible protein phosphorylation (catalyzed by kinases and phosphatases) in the malaria parasite Plasmodium are of great interest, for both increased understanding of parasite biology and identification of novel drug targets. Here, we report a functional analysis in Plasmodium of an ancient bacterial Shewanella-like protein phosphatase (SHLP1) found only in bacteria, fungi, protists, and plants. SHLP1 is abundant in asexual blood stages and expressed at all stages of the parasite life cycle. shlp1 deletion results in a reduction in ookinete (zygote) development, microneme formation, and complete ablation of oocyst formation, thereby blocking parasite transmission. This defect is carried by the female gamete and can be rescued by direct injection of mutant ookinetes into the mosquito hemocoel, where oocysts develop. This study emphasizes the varied functions of SHLP1 in Plasmodium ookinete biology and suggests that it could be a novel drug target for blocking parasite transmission.